Effects of AI on librarians' work performance: a systematic literature review - Iqbal, Abid; Masrek, Mohamad Noorman; Sahid, Noor Zaidi (Faculty of Information Management, 2025)
The study aimed to identify the effects of artificial intelligence on librarians’ work support. It also aimed to identify associated challenges for the efficient adoption of AI applications. SLR was applied as a methodology to address the study’s objectives. Findings revealed that AI has a significant positive impact on librarians’ work behavior. It supports them in delivering innovative information services. The study also manifested different challenges, including funding issues that cause problems for librarians to efficiently implement and sustain AI-based systems in library settings. The study has provided worthwhile theoretical, managerial, and social implications by identifying the effects of AI on librarians’ work performance. It has shown the impactful role of AI on the work productivity of librarians. It has provided insights for management bodies and relevant stakeholders to effectively utilize AI in library settings.